Retrospective study of foreign body-associated pathology in stranded cetaceans, Canary Islands (2000–2015) - Puig Lozano, Raquel; Diaz Delgado, Josue; García Álvarez, Natalia; Sierra Pulpillo, Eva María; De La Fuente Marquez, Jesus; Sacchini, Simona; Suarez Santana, Cristian Manuel; Succa, Daniele; Camara, Nakita; Saavedra Santana, Pedro; Almunia Portolés, Javier; Rivero Santana, Miguel Antonio; et al. (Environmental Pollution, 2018)
Marine pollution, overrepresented by plastic, is a growing concern worldwide. However, there is little knowledge on occurrence and detrimental impacts of marine debris in cetaceans. To partially fill in this gap of knowledge, we aimed to investigate the occurrence and pathologies associated with foreign bodies (FBs) in a large cohort of cetaceans (n = 465) stranded in the Canary Islands. The Canary Islands shelter the greatest cetacean biodiversity in Europe, with up to 30 different species, of which nine are regularly present year around. We found at least one ingested FB in 36 out of 465 (7.74%) studied cetaceans, involving 15 different species, including eight out of the nine (80%) cetacean species present year-round in the Canary Islands. Risso's dolphin was the species most affected, followed by sperm whale, beaked whale and mysticetes. Plastic FB were the most common item found (80.56%). FB was directly associated with death in 13/36 (36.11%) animals. Poor body condition and deep diving behavior were found to be risk factors for FB ingestion, whereas the adult age was a protective factor. To the authors knowledge this is the first study that use statistical analysis to investigate risk and protective factors for FB ingestion. This study also provides insights of the potential impact caused by ingested FBs on the animal's health and mortality. This knowledge is critical to better understand and assess the impact of FB in cetaceans setting the scientific basis for prospective impact monitoring and future conservation policies. 527 519 1,673 5,714 Q1 Q1 SCIE